2021
DOI: 10.1101/2021.08.09.455629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The miR-430 locus with extreme promoter density is a transcription body organizer, which facilitates long range regulation in zygotic genome activation

Abstract: In anamniote embryos the major wave of zygotic genome activation (ZGA) starts during the mid-blastula transition. This major wave of ZGA is facilitated by several mechanisms, including dilution of repressive maternal factors and accumulation of activating transcription factors during the fast cell division cycles preceding the mid-blastula transition. However, a set of genes escape global genome repression and are activated substantially earlier, during what is called, the minor wave of genome activation. Whil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Transcription bodies have been observed in multiple systems (Cisse et al 2013; Boehning et al 2018; Cho et al 2018; Ghamari et al 2013; Iborra et al 1996; Jackson et al 1998; Huang et al 2021; Hadzhiev et al 2021). It is unclear, however, what organizes their formation.…”
Section: Transcription Factors Cluster Prior To and Independent Of Tr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription bodies have been observed in multiple systems (Cisse et al 2013; Boehning et al 2018; Cho et al 2018; Ghamari et al 2013; Iborra et al 1996; Jackson et al 1998; Huang et al 2021; Hadzhiev et al 2021). It is unclear, however, what organizes their formation.…”
Section: Transcription Factors Cluster Prior To and Independent Of Tr...mentioning
confidence: 99%
“…Transcription by RNA polymerase II (RNA Pol II) takes place in concentrated areas in the nucleus, also called transcription bodies (Cisse et al 2013; Boehning et al 2018; Cho et al 2018; Ghamari et al 2013; Iborra et al 1996; Jackson et al 1998; Huang et al 2021; Hadzhiev et al 2021). Recently, it has been shown that clusters of RNA Pol II and Mediator localize to such transcription bodies (Cho et al 2018).…”
mentioning
confidence: 99%